Distribution, identification and cytotoxicity of Gambierdiscus (Dinophyceae) in the Atlantic Selvagens Islands (Madeira, Portugal): a ciguatera gateway to Europe. Issue 2 (3rd April 2023) - Godinho, Lia; Soliño, Lucía; Churro, Catarina; Timoteo, Viriato; Santos, Carolina; Gouveia, Neide; Diogène, Jorge; Reis Costa, Pedro
ABSTRACT: The emerging threat of ciguatera poisoning (CP) in Europe has been associated with fish captured in the Canary Islands (Spain) and Selvagens Islands (Portugal). The first are heavily populated islands where numerous scientific studies have been carried out. Conversely, the Selvagens Islands as a nature reserve with low human pressure have been rarely surveyed in terms of the marine benthic microalgae, including the epiphytic ciguatera-causing dinoflagellate species. To investigate the harmful microalgal diversity of the Selvagens Islands, a scientific cruise to these remote islands took place in September, 2018. The Gambierdiscus species composition and distribution, and the associated epiphytic dinoflagellate community, were assessed using artificial substrate devices. Gambierdiscus cells were found in all samples, reaching concentrations of up to 725 cells 100 cm –2 . G. australes was the only species identified after morphological and molecular analysis of the retrieved cultures. Species identification was confirmed by molecular characterization based on the LSU D8–D10 region. Nevertheless, phylogenetic studies indicated that some strains diverged from the G. australes clade suggesting genetic differentiation. Toxicity was estimated by neuro-2a cell-based assay in four strains, ranging from 2.46–83 fg of CTX1B eq. cell –1 . The epiphytic dinoflagellate community that co-occurred with Gambierdiscus comprised other toxic or potentially toxic dinoflagellates, such as Ostreopsis, Prorocentrum, Amphidinium and Coolia species. Oceanographic and meteorological data were also obtained to characterize the occurrence of Gambierdiscus . This study is the first stage in understanding the role of the Selvagens Islands in the incubation and proliferation of the ciguatera-causing dinoflagellates Gambierdiscus in the NE Atlantic. Highlights: The Selvagens Islands are a ciguatera hotspot in Europe. Gambierdiscus australes was the only species observed in the Selvagens Islands. Strains diverging from the G. australes clade suggest genetic differentiation.